Trends in Sports Marketing. - Čáslavová, Eva. (Karolinum Press, 2025)
This publication explores the evolution and trends in sports marketing, focusing on global and Czech contexts. It examines megatrends such as income and wealth, leisure time, changing societal values, technological advancements, and urbanization, which influence the development of sports marketing. The book delves into digital marketing strategies, the role of sports celebrities in marketing, and the marketing of sports services, highlighting their growth and future potential. It provides insights into strategic and tactical marketing approaches, emphasizing the importance of branding, sponsorship, and innovation in the sports industry. The work is intended for students and professionals seeking to understand and apply sports marketing concepts effectively.